2007
DOI: 10.1103/physrevd.75.083007
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling hidden patterns in CMB anisotropy maps

Abstract: Bianchi VII h models have been recently proposed to explain potential anomalies in the CMB anisotropy as observed by WMAP. We investigate the violation of statistical isotropy due to an embedded Bianchi VII h template in the CMB anisotropy maps to determine whether the existence of a hidden Bianchi template in the WMAP data is consistent with the previous null detection of the bipolar power spectrum in the WMAP first-year maps. We argue that, although correcting the WMAP maps for the Bianchi template may expla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 49 publications
1
73
0
Order By: Relevance
“…A number of authors have attempted to explain the observed quadrupole-octopole correlations in terms of a new foreground [51][52][53][54][55][56]. (Some of these also attempted to explain the absence of large angle correlations, for which there are also other proffered explanations [57][58][59][60][61][62][63].)…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have attempted to explain the observed quadrupole-octopole correlations in terms of a new foreground [51][52][53][54][55][56]. (Some of these also attempted to explain the absence of large angle correlations, for which there are also other proffered explanations [57][58][59][60][61][62][63].)…”
Section: Discussionmentioning
confidence: 99%
“…(20). It is obvious that the contributions of these time dependent terms to the energy cannot compensate the infinite value of (P 0 ) 2 corresponding to the constant mode, which implies that the total contribution to (P 0 ) 2 due to the j = 2 k-interval cannot become finite.…”
Section: A Scalar Perturbationsmentioning
confidence: 99%
“…A modified template fitting technique was performed by Land & Magueijo (2006) and, although a statistically significant template fit was not reported, the corresponding "corrected" WMAP data were again free of many large scale "anomalies". Subsequently, Ghosh et al (2007) used the bipolar power spectrum of WMAP data to constrain the amplitude of any Bianchi component in the CMB. Due to the renewed interest in Bianchi models, solutions to the CMB temperature fluctuations induced in Bianchi VII h models when incorporating dark energy were since derived by Jaffe et al (2006c) and Bridges et al (2007).…”
Section: Previous Resultsmentioning
confidence: 99%